Investigation of the Tool Wear Progression in Parting Technology - Drbal, Martin; Kolomy, Stepan; Sedlak, Josef; Zouhar, Jan; Vitek, Jiri (Manufacturing Technology Journal, 2024)
Parting-off stands as a fundamental method of turning, involving the cutting of the workpiece. The tool is most frequently a replaceable insert secured in a clamping bed. A pivotal set of observable metrics that ascertain the efficacy of a tool and its appropriateness for machining a specific material under defined cutting conditions is its durability. These durability parameters need to be determined for all new tools to ensure optimal performance and application in various machining scenarios. The primary objective of this research was analysis of the wear experienced by replaceable cutting inserts within the realm of parting technology. There were three distinct variants of replaceable cutting in-serts, all produced by esteemed manufacturer Dormer Pramet s.r.o. These cutting inserts were ap-plied in the parting process, consecutively machining two materials: bearing steel 100Cr6 and stainless steel 316L. The study not only encompasses the description of the cutting test procedure but also involves the meticulous execution of measurements and the subsequent analysis of the data procured from experimental activities. In the final phase of study, additional analyses are outlined to uncover the factors contributing to variations in certain obtained results. Those analyses, such as material or tool coatings analysis, provides more information about interplay between replaceable cutting inserts and the specific materials subjected to parting processes.
Keywords: Parting-off technology; Cutting insert; Tool wear; Durability; Tool coating